ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN PENDEKATAN RGEC (RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, CAPITAL) - Dewi, Meutia (Fakultas Ekonomi dan Bisnis Islam, 2018)
This study aims to determine the soundness of the bank at PT. Bank Rakyat Republik, Tbk which is seen from risk profile factors, good corporate governance, earnings, and capital during the period 2013-2017. The method of data analysis in this study is descriptive analysis with a quantitative approach. In the results of data analysis, it can be explained that the soundness of the bank at PT. Bank Rakyat Indonesia, Tbk, judging from the risk profile factor, shows that the bank's NPL below 2% with a very healthy predicate and the majority of bank LDR predicate is quite healty. The factor of good corporate governance shows that the bank has a very trusted title. The earnings factor shows that bank ROA of more than 1.5% with a very healthy predicate and bank NIM of more than 3% with a very healthy predicate. The capital factor shows that the bank CAR of more than 12% has a ver healthy predicate. So that the assessment of the soundness of the bank at PT. Bank Rakyat Indonesia, Tbk seen fromrisk profile factors, good corporate governance, earnings, and capital during the period 2013-2017 with an average value of 93,99% included in the category of â€œVery Healthyâ€ or composite rating 1 (PK-1)